Experiments On Sublimating Carbon Dioxide Ice And Implications For Contemporary Surface Processes On Mars. Issue 1 (December 2017) - Mc Keown, L.; Bourke, M.; McElwaine, J.
Abstract Carbon dioxide is Mars' primary atmospheric constituent and is an active driver of Martian surface evolution. CO2 ice sublimation mechanisms have been proposed for a host of features that form in the contemporary Martian climate. However, there has been very little experimental work or quantitative modelling to test the validity of these hypotheses. Here we present the results of the first laboratory experiments undertaken to investigate if the interaction between sublimating CO2 ice blocks and a warm, porous, mobile regolith can generate features similar in morphology to those forming on Martian dunes today. We find that CO2 sublimation can mobilise grains to form (i) pits and (ii) furrows. We have documented new detached pits at the termini of linear gullies on Martian dunes. Based on their geomorphic similarity to the features observed in our laboratory experiments, and on scaling arguments, we propose a new hypothesis that detached pits are formed by the impact of granular jets generated by sublimating CO2 . We also study the erosion patterns formed underneath a sublimating block of CO2 ice and demonstrate that these resemble furrow patterns on Mars, suggesting similar formation mechanisms.